REVIEW ON FAKE INDIAN CURRENCY RECOGNITION TECHNIQUES - Chhaya Wani; Sheetal Gunda (International Journal of Innovations in Engineering Research and Technology, 2021)
The paper proposes a review on Fake Indian Currency Recognition techniques to detect mal practicing. In the country, the problem is in acute situation because of counter less activities of people involved in the rackets. Counterfeiting problems occurs over a time due to technological advances in color printing, duplicating and scanning. Fake currency notes of Rs.100, Rs.500 and Rs.1000 are highly detected.